2020
DOI: 10.1111/jgs.16767
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregivers of Veterans Experience High Levels of Burden, Distress, and Financial Strain

Abstract: BACKGROUND/OBJECTIVES: To describe the caregiving experiences and physical and emotional needs of family members and friends who provide care to veterans with mental, physical, and cognitive comorbidities. DESIGN: Cross-sectional study. SETTING: National telephone surveys administered from 2017 to 2019. PARTICIPANTS: Family caregivers of veterans enrolled in the Veterans Affairs (VA) Program of General Caregiver Support Services between October 2016 and July 2018 who responded to a telephone survey (N = 1,509;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
(115 reference statements)
2
24
0
Order By: Relevance
“…When one considers the financial savings mentioned earlier, with informal caregiving relieving the NHS of around £152 billion in care per year [ 47 ], it is devastating to think that the informal caregivers are provided with far less than a minimum wage job per week in order to provide this care, especially with the current cost of living crisis. Therefore, it comes as no surprise that the financial strains associated with informal caregiving have been linked to mental ill health and physical ill health within these informal caregivers [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…When one considers the financial savings mentioned earlier, with informal caregiving relieving the NHS of around £152 billion in care per year [ 47 ], it is devastating to think that the informal caregivers are provided with far less than a minimum wage job per week in order to provide this care, especially with the current cost of living crisis. Therefore, it comes as no surprise that the financial strains associated with informal caregiving have been linked to mental ill health and physical ill health within these informal caregivers [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research has demonstrated the negative impacts of service on the health and well-being of family members of veterans (Cramm et al, 2015;Forrest et al, 2018;Shepherd-Banigan et al, 2020). This serving member, so comparisons were unable to be made between carers of current and former serving personnel; however, this is an avenue that should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated the negative impacts of service on the health and well‐being of family members of veterans (Cramm et al., 2015; Forrest et al., 2018; Shepherd‐Banigan et al., 2020). This is further supported by the Productivity Commission (Australian Government Productivity Commission, 2019), who recommended that more research is required to understand the impact of service on the mental health and well‐being of veterans' families.…”
Section: Discussionmentioning
confidence: 99%
“…We conduct secondary analysis of existing survey data, thus we examine measures selected by the VA Caregiver Support Program Partnered Evaluation Center as informed by adopting the Organizing Framework for Caregiver Interventions 32,38,39…”
Section: Methodsmentioning
confidence: 99%